2020
DOI: 10.3390/su12031184
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Online Reputation and Positioning of Airlines

Abstract: The aim of this study is to propose a methodology to define the positioning of airlines in terms of their online reputation measured with quantitative variables and applied in the airline industry. Reviews shared on the Internet give key information about service quality and value as perceived by customers. To carry out the empirical study, we obtained the information available on TripAdvisor about airlines in Europe, the USA, Canada, and other countries in America, differentiating also between airlines that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 84 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…In the context of the airline industry, managers can use this dynamic method to identify the different labels to achieve the maximum customer satisfaction across time and position their service offerings. Our findings are in line with the literature on the important role of Big Data in providing airlines with a sustainable competitive advantage [12,96,97]. The practical implications of this study have strategic relevance for airlines.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the context of the airline industry, managers can use this dynamic method to identify the different labels to achieve the maximum customer satisfaction across time and position their service offerings. Our findings are in line with the literature on the important role of Big Data in providing airlines with a sustainable competitive advantage [12,96,97]. The practical implications of this study have strategic relevance for airlines.…”
Section: Discussionsupporting
confidence: 89%
“…The online reputation is the basis for the different research lines being developed to improve knowledge and provide useful tools for airlines to better understand their clientele's preferences and the competitiveness of their service offerings [11,12]. The objective is for the image transmitted by companies on the Internet through social media and specialized websites to correspond to the service perceived by customers [13].…”
Section: Introductionmentioning
confidence: 99%
“…They found geographic and low-cost strategy differences in service quality. They identified 295 significant tags associated with overall ratings [22]. Lucini et al used text-mining techniques on over 55,000 online reviews from 170 countries, representing over 400 airlines.…”
Section: Latent Dirichlet Allocationmentioning
confidence: 99%
“…The issue of online reputation assessment is not new; over time, it has become the subject of several international regulations and standards. Studies and research conducted in recent years showed that a company's online reputation strongly affects CSR consumer interpretations because the company is more accepted and credible when engaging in CSR [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%